Deteksi antibodi trombosit spesifik anti-hpa-3 pada neonatus dengan trombositopenia - Arum Margi Kusumawardani; Ken Ritchie, Ni; Amalia Wahidiyat, Pustika (MEDIA ILMU KESEHATAN, 2021)
Background: The immune factor causing thrombocytopenia in neonates can occur even during pregnancy. Antigen discrepancies in the platelet membrane expressed by the fetus and maternal can be the cause of thrombocytopenia. This is due to the presence of anti-platelet antibodies produced by the maternal body as a form of immune response after exposure to antigens on the platelet membrane expressed by the fetus. Human platelet antigen detection has not been carried out in Indonesia, there is no known antigen on the platelets. This allows the occurance of alloimmune thrombocytopenia in neonates, one of sign that can be recognized through clinical symptoms was neonates with thrombocytopenia. Screening anti-platelet antibodies in neonates with thrombocytopenia is an effort to find the possibility of anti-human platelet antigen antibodies. Objective: The aim of this study is to find out the presence of anti-platelet antibodies in neonates with thrombocytopenia. Methods: The study is descriptive observational with cross sectional design. The subject in this study were neonates with thrombocytopenia according to the study criteria. The collected sample is screened for the presence of anti-platelet antibodies, then identification of anti-HPA antibodies. Results: Screening in 30 neonates showed that 3 neonatal positive anti-platelet antibodies, 2 with borderline and 25 negative anti-platelet antibodies. Identification of anti-platelet antibodies was performed in five samples (result of screening, three with positive screening and two borderline), indicating that all were negative for the anti-human platelet antigen antibody GPIIb/IIIa specific HPA-3. Conclusion: Based on the screening result, five samples were found to have anti-platelet antibodies in neonates with thrombocytopenia, but after identification none of them were found to be specific anti-HPA antibodies to GPIIb/IIIa.